La planificación presupuestaria necesaria para determinar las utilidades futuras. - Chamba Rendon, Alvaro Gabriel (My University, 2020)
The management of the companies involves the use of different tools that allow us to understand the financial behavior of the organization, being essential that the results to be obtained are part of the accounting planning that is carried out within a company, in this virtue it was proposed as evidence objective the importance of budget planning through the preparation of financial statements to project the utility to be achieved after an economic year. The methodology had a qualitative approach and the sustenance information was disaggregated through the method of synthesis analysis, which provided the theoretical basis to understand the problem in order to focus efforts to achieve the objectives. The results through the proposed scenario established the importance of carrying out the financial planning as well as correctly quantifying the processes that are carried out within the company, in order to make a correct control of the financial accounts and be the contribution that is required for making decisions. These decisions contribute to maximizing profits, increasing revenues and minimizing costs, in order to seek more efficient production.
La gestión de las empresas involucra al uso de diferentes herramientas que permiten entender el comportamiento financiero de la organización, siendo fundamental que los resultados a obtener sean parte de la planificación contable que se realizan dentro de una empresa, en tal virtud se planteó como objetivo evidenciar la importancia de la planificación presupuestaria a través de la elaboración de estados financieros para proyectar la utilidad a alcanzarse después de un ejercicio económico. La metodología tuvo un enfoque cualitativo y la información de sustento fue desagregada a través del método de análisis síntesis, la cual aportó con la base teórica para entender el problema a fin de focalizar esfuerzos para el cumplimiento de los objetivos. Los resultados a través del escenario propuesta establecieron la importancia de realizar la planificación financiera además de cuantificar correctamente los procesos que se realizan dentro de la empresa, a fin de realizar un correcto control de las cuentas financieras y ser el aporte que se requiere para toma de decisiones. Estas decisiones tributan a la obtención de maximizar utilidades, logrando incrementar los ingresos y minimizar los costos, a fin de buscar producción más eficiente.
Keywords: PLANIFICACIÓN FINANCIERA; UTILIDADES; GESTIÓN CONTABLE